1980
DOI: 10.1002/jobm.19800200503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the antimicrotubular cancerostatic drug nocodazole on the yeast Saccharomyces cerevisiae

Abstract: Nocodazole completely inhibited cell division of Saccharomyces cerevisiae, contrary to methylbenzimidazole‐2‐ylcarbamate, estimated by cell counting. Growth as measured by turbidity and dry weight estimations, however, was not influenced. Treatment for two hours with nocodazole interrupts the budding cycle of the yeast within a period when bud and mother cells have reached equal sizes. Dependent on duration of nocodazole treatment stretched or dumb‐bell shaped nuclei are localized between bud and mother cell o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…IN–GFP‐ expressing yeast cells were grown overnight to reach stationary phase and to prevent cell division. Then the cells were treated with the drug for 1 h. As described by Kunkel (1980), we observed a mitotic arrest of cells with an accumulation of budded forms in the presence of nocodazole (Figure 4A). Moreover, the observation shows that the only perinuclear fluorescent spot in non‐treated cells broke into several sparks (up to five; Figure 4A).…”
Section: Resultssupporting
confidence: 70%
“…IN–GFP‐ expressing yeast cells were grown overnight to reach stationary phase and to prevent cell division. Then the cells were treated with the drug for 1 h. As described by Kunkel (1980), we observed a mitotic arrest of cells with an accumulation of budded forms in the presence of nocodazole (Figure 4A). Moreover, the observation shows that the only perinuclear fluorescent spot in non‐treated cells broke into several sparks (up to five; Figure 4A).…”
Section: Resultssupporting
confidence: 70%
“…Clustering Chemical-Genetic Profiles for Compounds with Similar Modes-of-Action and Genes with Similar Function We found that compounds with similar cellular effects showed similar chemical-genetic profiles and thereby cluster together on the vertical axis in Figure 1, revealing both anticipated and novel insights into their mode-ofaction. In particular, there are a number of examples where the cluster analysis groups compounds known to inhibit the same pathway or target (Figure 1, individual clusters indicated by roman numerals): (i) actin binding agents latrunculin B (Ayscough et al, 1997) and cytochalasin A (Torralba et al, 1998); (ii) cell wall synthesis inhibitors staurosporine, which targets Protein kinase C, a regulator of a MAP kinase cascade involved in cell wall metabolism (Yoshida et al, 1992), and caspofungin, which inhibits 1,3 b-glucan synthase (Douglas et al, 1994b); (iii) nystatin (Hosono, 2000) and amphotericin (Aoun, 2000), both of which act by increasing the permeability of the fungal cell membrane; (iv) clotrimazole and fluconazole, chemical analogs and antifungal agents that target Erg11 (Fromtling, 1988;Truan et al, 1994), a protein encoded by an essential gene in the ergosterol biosynthesis pathway; (v) radicicol and geldanamycin, although structurally unrelated, both act as highly selective inhibitors of Hsp90 function through their ability to bind within the ADP/ATP binding pocket of the chaperone (Roe et al, 1999); (vi) benomyl (Thomas et al, 1985) and nocodazole (Kunkel, 1980), two microtubule poisons; (vii) haloperidol (Moebius et al, 1996), fenipropimorph (Marcireau et al, 1990), and dyclonine (Hughes et al, 2000), are all thought to inhibit Erg2 function in yeast. Deletion mutants with similar chemical sensitivities also cluster together on the horizontal axis of Figure 1, grouping functionally related genes (Figure S1).…”
Section: Two-dimensional Hierarchical Clustering Analysismentioning
confidence: 99%
“…To test whether intracellular movement and lipid droplet degradation was dependent on the cytoskeleton, cells were treated with nocodazol (Kunkel, 1980) or latrunculin A (Ayscough et al, 1997) (supplementary material Fig. S3).…”
Section: The Dynamic Spatial Distribution Of Lipid Droplets In Growinmentioning
confidence: 99%